Analisis Yajna Sebagai Dasar Pengembangan Mutu Karakter Peserta Didik Di Sekolah Menengah Pertama Gurukula - Ketut Nurhayanti; Putu Adi Suprapto (UHN IGB Sugriwa Denpasar, 2018)
This study is to analyze the teachings of yajna as the basis for the character formation of learners in Gurukula Junior High School. As a school that implements the pasraman education system, the Gurukula Junior High School in making the program of activities that will be applied in schools is always based on religious teachings. This research use qualitative research method by using research instrument of interview, observation and also documentation study. The results of data analysis in this study using qualitative description. The result of this study is that the yajna teachings applied in the First Middle School Gurukula is a simple yajna teaching such as cleaning the pasraman environment, cooking for all residents of the dorm, greeting every visitor. The activity is very effective to form and develop the good character of learners like honest, responsible, independent, friendly and polite, discipline and so forth.